Social welfare in the Greco-Roman world as a background for early Christian practice - Lampe, Peter (Acta theologica, 2016)
The essay investigates if and how Greco-Roman theorists attempted to motivate altruistic behaviour and devise a social-welfare ethics. In comparison, it studies actual social-welfare practices on both the private and the state level. Various social-welfare tasks are touched upon - health care; care for the elderly, widows, orphans and invalids; the patron-client system as countermeasure to unemployment; distribution of land, grain, meals and money; alms, donations, foundations as well as education - with hardly any one of them being especially tailored to the poor. The enormous role of civil society - private persons, their households and associations - in holding up social-welfare functions is shown. By contrast, the state was comparatively less involved, the commonwealth of the Romans, especially in Republican times, even less than the Greek city-states. The Greek poleis often invested income such as wealthy citizens’ donations in social welfare, thus brokering between wealthy private donors and less well-to-do persons. The church, living in private household structures during the first centuries, took over the social-welfare tasks of the Greco-Roman household and reviewed them in the light of Hebrew and Hellenistic-Jewish moral traditions.